Methodology for Compiling Hadith in the 4th Century Hijri: Integrating Transmission and Practical Orientation in Ibn Sunnī’s Work - Nasution, Ismail; Zuhri, Ahmad; Ardiansyah, Ardiansyah; Manik, Zulfirman (Diroyah : Jurnal Studi Ilmu Hadis, 2025)
The development of hadith codification in the 3rd to 4th centuries of the Hijri marked an increasingly complex process of systematising the transmission of religious knowledge through various hadith compilations. However, modern hadith studies tend to focus on the criticism of the sanad (chain of transmission) and the evaluation of narrators’ authority. In contrast, the methodological dimensions of compilation methods, thematic organisation, and the practical orientation of hadith compilations are less thoroughly analysed. This gap is particularly evident in studies of the works of 4th-century Hijri scholars who integrated the legitimacy of sanad transmission with the practical needs of the community. This study aims to analyse the methodology of hadith compilation in the works of Ibn Sunnī and to explain how the integration of the legitimacy of sanad transmission and a practical orientation shaped the structure of hadith compilations during that period. The study uses a qualitative approach, with textual analysis and the historiography of hadith, through an examination of the thematic structure of the books, the configuration of the sanad transmission network, and variations in hadith redaction in Ibn Sunnī’s works. The results show that Ibn Sunnī’s compilation methodology exhibits three main characteristics. First, the pattern of hadith transmission relies on a broad and multi-layered network of teachers that strengthens the legitimacy of the sanad and reflects intellectual mobility within the 4th-century AH transmission network. Second, the hadith compilation is structured thematically, with a strong orientation towards worship, prayer, and daily ethics, so that it functions as a practical guide for the religious life of Muslim communities. Third, the text’s editing strategy preserves variations in hadith redactions across different transmission lines, representing the dynamics of transmission in the oral and written traditions. These findings suggest that Ibn Sunnī’s compilation functioned not only as an archive of sanad transmission but also as a pedagogical tool that connects scholarly authority with the religious needs of the community, thus making an important contribution to the understanding of the historiography and methodology of classical hadith compilation